Development of Quality Identification of Granules based on Flow Time using Infrared Proximity Sensor and Arduino - Fadlil, Abdul; Riadi, Imam; Yusmianto, Ferry (Jurnal Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
Abstract — The evaluation of granule quality before mixing into tablets includes testing moisture content, static angle, compressibility, and flow rate. Good flowability is essential for granules intended for tablet compression, as it facilitates smooth compression and ensures uniform mold filling, impacting the consistency of tablet weight and active ingredient content. Granule flow rate is measured based on the time required for a certain amount of granules to flow through a funnel, with a good flow time standard being under 10 seconds or 10 g/second. Traditional methods use a stopwatch to measure flow rate, but this study introduces an automated system based on an infrared proximity sensor and Arduino for more accurate and efficient results. Experiments were conducted with two types of granules, red and white, to test this tool’s performance. Based on measurement results, the Arduino-based tool showed a low error rate compared to the stopwatch, with an average of 1.28% for red granules and 1.03% for white granules. These findings demonstrate that this automated system can reliably measure granule flow rate, improve accuracy, and reduce the potential for manual error.